Structure and evolution of the Atlantic passive margins: A review of existing rifting models from wide-angle seismic data and kinematic reconstruction. (April 2021) - Biari, Youssef; Klingelhoefer, Frauke; Franke, Dieter; Funck, Thomas; Loncke, Lies; Sibuet, Jean-Claude; Basile, Christophe; Austin, James A.; Rigoti, Caesar Augusto; Sahabi, Mohamed; Benabdellouahed, Massinissa; Roest, Walter R.
Abstract: Deep seismic data and plate kinematic reconstructions help understand the mechanisms of rifting and opening of new oceans, basic principles of plate tectonic cycles. In this study, available deep wide-angle seismic velocity models from the Atlantic margins are reviewed and plate reconstructions used to define conjugate model pairs. The main objective was to study the question of how magma-rich and magma-poor margins develop and the role of inheritance in the break-up. We also studied the question of the mechanism of formation and the origin of transform marginal plateaus, which are typically found at the border of two ocean basins of different ages and are mostly characterized by at least one volcanic phase during their formation. The results of the study include the comparison of crustal thickness, oceanic plate thickness and the influence of volcanism along the Atlantic margins. The conjugate profiles image different degrees of asymmetry of the Atlantic Margin rifts. Marginal plateaus might form when rifting stops at barriers leading to the accumulation of heat in the mantle and increased volcanism directly before or after halting of the rifting. Highlights: Deep seismic velocity models, plate kinematic reconstructions and geological information are used. Rifting styles and volcanic influence along the Atlantic Margins are studied. Zones of exhumed and serpentinized upper mantle had been discovered only at magma-poor margins. At magma-rich margins the volume of magma is largest close to transfer zones and decreases in the direction of rifting. Sheared margins are often associated with transform marginal plateaus, which have undergone at least one volcanic phase.